An Empirical Analysis of Psychological and Statistical Patterns in Narcissistic Traits and Romantic Partner Selection - Ahmed Ejaz; Iqra Rahim Sahibzada; *Mazhar Ali; Syed Hassan Abrar; Amara Gul; Syed Ibrahim (Review Journal of Social Psychology & Social Works, 2025)
This study explores the relationship between narcissistic personality traits and partner selection tendencies among university students, offering a reflective examination of how these traits shape romantic preferences. By investigating the variables: overt, covert, and sexual narcissism, the research seeks to uncover the psychological foundation of attraction and partner selection. The notion that narcissism is “felt” highlights the subjective nature of its influence, suggesting that personal perceptions and lived experiences play a role in romantic decision-making. Employing advanced statistical methodologies, including regression analysis and interdependence measures, the study evaluates the strength and significance of these associations. The findings build up the idea that personality traits are rooted in romantic preferences, offering a thorough understanding of how attraction is both psychologically and statistically substantiated. By analyzing the role of narcissistic tendencies in relationship dynamics, this research enhances the comprehension of how personality constructs shape interpersonal behavior and romantic choices.